METHODOLOGY FOR OPTIMIZING THE LAYOUT OF ROOMS AND PILLARS – CASE STUDY URUCUM MINE - NASCIMENTO, LUCAS (2023)
For design of rooms and pillars in underground mining, traditional design methods are commonly used, which is not usually configured as the premise of the best geometry for maximum ore extraction. As an alternative, presents at a proposal for optimized layout redesign of rooms and pillars of a defined area at Urucum mine, a manganese mine, located in Corumbá-MS. This is possible by establishing ore recovery functions, whose variables are geometric with geotechnical and operational constraints. The combination of these recovery functions and constraints can be mathematically encoded in non-linear programming algorithms, with the main objective of maximizing mine recovery and obtaining the greatest possible utilization of the ore body. As a result of the optimization process using nonlinear mathematics, a new mine layout with higher profitability and maintenance of operational safety conditions is obtained.